Antibacterial Activity of Pasak Bumi Stem (Eurycoma longifolia J.) Extract against Salmonella typhi - Sirait, Christine; Hanasia, Hanasia; Martani, Natalia Sri; Ysrafil, Ysrafil; Fatmaria, Fatmaria (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Typhoid fever is caused by consuming food or water contaminated with Salmonella typhi. The disease develops from bacterial infection through the consumption of contaminated sustenance and drink. The bacterium can cause bacteremia, which is bacteria living in the blood, penetrating the mucosal epithelium of the small intestine and entering the lymphatic flow. Therefore, this study aimed to assess the potential inhibitory effect of ethanol extracts derived from stems of Eurycoma longifolia (pasak bumi) on the growth of Salmonella typhi bacteria. Compounds such as alkaloids, saponins, flavonoids, terpenoids, and tannins in pasak bumi stems possessed antibacterial properties. Extracts were made using 96% ethanol at varying concentrations (10%, 20%, 30%, 40%, 50%) with distilled water and chloramphenicol as negative and positive control. The result showed that pasak bumi stem extracts inhibited Salmonella typhi, with increasing efficacy at higher concentrations and statistical analysis reported significant differences between all treatment groups (p<0.001). Average zone diameter was 0 mm and 23.10 mm for negative and positive control, as well as 2.75 mm, 4.10 mm, 5.24 mm, 6.98 mm, and 8.55 mm for 10%, 20%, 30%, 40% and 50% extracts, respectively. This study provided verification of antibacterial effects of pasak bumi stem ethanol extracts against Salmonella typhi.